1997
DOI: 10.1007/bf03161407
|View full text |Cite
|
Sign up to set email alerts
|

Response of benthic and planktonic algal biomass to experimental water-level manipulation in a prairie lakeshore wetland

Abstract: The quantitative contribution of benthic (periphytic) and planktonic algae to primary production in prairie wetlands is largely unknown, as is their response to the fluctuations in water level that characterize such systems. We measured the biomass (chlorophyll-a m -2 of wetland area) of phytoplankton, epipelon, epiphyton, and metaphyton in Delta Marsh, Manitoba as part of a five-year study in which diked, drawn down cells were reflooded to ~e normal level of the wetland, or to a depth 30 cm or 60 cm deeper. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
(37 reference statements)
3
17
0
Order By: Relevance
“…In more productive wetland systems, however, mid-summer, and even fall, maxima may occur (Crumpton 1989). In fact, the timing of biomass and production peaks reported here is similar to those recorded for productive wetlands at Delta Marsh, Manitoba (Robinson et al 1997). There are a number of possible explanations for this phenomenon.…”
Section: Seasonal Variation In Biomass and Productionsupporting
confidence: 82%
“…In more productive wetland systems, however, mid-summer, and even fall, maxima may occur (Crumpton 1989). In fact, the timing of biomass and production peaks reported here is similar to those recorded for productive wetlands at Delta Marsh, Manitoba (Robinson et al 1997). There are a number of possible explanations for this phenomenon.…”
Section: Seasonal Variation In Biomass and Productionsupporting
confidence: 82%
“…and water depth was unexpected and suggested that relatively more light reached the sediments in deep than in shallow water. Profuse epiphyton, metaphyton, and macrophytes can reduce water transparency and we found that algal productivity (Figures 5, 6) and biomass (Robinson et al 1997) also varied inversely with water depth. Thus, high light extinction in shallow waters was probably a consequence of high macrophyte, metaphyton, and epiphyton biomass.…”
Section: Variation In Photosynthetic Parametersmentioning
confidence: 85%
“…This procedure incorporated regular estimates of algal biomass expressed as area-based chlorophyll-a (Table 1; Robinson et al 1997), numerical relationships between biomass-normalized carbon assimilation rates (specific productivity) and irradiance, and measurements of ambient photosynthetically active radiation (PAR).…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations